(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Local communities are in need of self-resources so that they can perform their multiple functions which serve the objectives of the local development, and tax revenues are considered as important sources of their funding. However, despite the efforts of the state to reform the fiscal system and to improve the management in the local administration, tax collection can increase when the state adopts a more effective policy to combat tax evasion and tax fraud. Accordingly, this research aims to shed light on the role of local tax revenues in the local development. A set of conclusions are drawn; the most important one is that Algeria, in order to achieve local development, has taken a set of reforms, which are still valid until now. The most important reform is the imposition of a set of taxes and fees whose revenues return, whether wholly or partly, for the benefit of the local communities. We also come to the conclusion that despite the importance of the fee charged on the professional activity in the budget of the province of Tebessa because of being the only fee that returns its revenues entirely to the local communities, it has experienced a steady decline from 2011 to 2014. This decline reflects the lack of projects in thisprovince in addition to the weak control over tax collection.